2002
DOI: 10.1046/j.1460-9592.2002.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ilioinguinal nerve block on the catecholamine plasma levels in orchidopexy: comparison with caudal epidural block

Abstract: The result of this study revealed that caudal epidural block was more effective than ilioinguinal block in suppressing the stress response as reflected in epinephrine and norepinephrine blood levels in orchidopexy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
3
28
0
1
Order By: Relevance
“…Five patients (33.3%) from ILIH block group, who had a pain score of greater than five, received i.v. fentanyl in the PACU [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five patients (33.3%) from ILIH block group, who had a pain score of greater than five, received i.v. fentanyl in the PACU [30].…”
Section: Discussionmentioning
confidence: 99%
“…In all these studies, the authors used single "pop" sensation techniques, injecting local anesthetics under external oblique muscle aponeurosis, with failure rates ranging from 25.8% to 33% [31,1,2,28,30]. In Kundra's study, injection of the local anesthetics above and below internal oblique muscle aponeurosis demonstrate a success rate of 94% [29].…”
Section: Discussionmentioning
confidence: 99%
“…Looking specifically at regional anaesthesia for orchidopexy, some studies suggest a superiority of caudal block over IIB (without the addition of SCB) [20,21]. Somri measured plasma catecholamines in 30 boys randomised to IIB or caudal block for orchidopexy [20].…”
Section: Discussionmentioning
confidence: 99%
“…Somri measured plasma catecholamines in 30 boys randomised to IIB or caudal block for orchidopexy [20]. Considering these hormones as an objective surrogate for pain and anxiety, significantly lower levels were found in the caudal group post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Rogers et al [59][60][61][62] confirmed the benefits of neuroaxial blockade with or without concomitant general anaesthesia in terms of reducing postoperative mortality and morbidity in the adult population. Epidural anaesthesia suppresses serum levels of stress hormones in children undergoing lower abdominal surgery, whereas general inhalational anaesthesia alone or general anaesthesia with low-dose intravenous opioids appears to be ineffective in suppressing the surgical stress response [63][64][65].…”
Section: Anaesthetic Techniquementioning
confidence: 99%